Research progress on m6A demethylase FTO and its role in gynecological tumors - Wang, SiYuan; Liu, Qin (Frontiers in Oncology, 2024)
Recent advances in genomic research have increasingly focused on the fat mass-and obesity-associated (FTO) gene due to its notable correlation with obesity. Initially explored for its contribution to increased body weight, FTO was later discovered to function as an m6A demethylase. This pivotal role enhances our understanding of its broader implications across various pathologies. Epigenetic modifications, such as m6A, have been implicated in gynecological cancers, including ovarian, endometrial, and cervical malignancies. However, the precise mechanisms by which FTO influences the development of gynecological cancers remain largely unknown. This analysis underscores the growing relevance of investigations into the FTO gene in elucidating the mechanisms underlying gynecological cancers and exploring potential therapeutic avenues.The initial focus on the FTO gene was due to its link with obesity, and for an extended period, the impact of obesity on various diseases has been a prominent research topic.Recently, the FTO has emerged as a pivotal subject of study (1-3). A pivotal advancement in the field of epitranscriptomics was achieved with the characterization of FTO as the inaugural m6A demethylase, capable of facilitating dynamic and reversible epigenetic modifications. This discovery has opened new avenues for understanding how genetic information can be regulated post-transcriptionally in a reversible manner. FTO has been implicated in the invasion, migration, and proliferation of tumors across several cancers and is influenced by m6A levels.Research has shown that FTO is involved in critical processes, such as malignant tumor development, immunosuppression, glycolysis, drug resistance, angiogenesis, epithelial-mesenchymal transition, metastasis, and cancer cell proliferation (4-7).Given its significant role in these diverse processes, FTO is a promising target for the detection and management of gynecological tumors including ovarian, endometrial, and cervical cancers.